Linking economic development and spatial planning in South Africa : a case study of state-market relations in Cape Town - Higginson, Lisa (School of Economics, 2016)
In South African cities institutional practices and market forces are seen to reinforce spatial divisions. This dissertation reflects on the relationship between location fixed resources, market forces and state intervention and how the interaction of these factors influence urban spatial outcomes. It first develops the underlying economic theory that could inform good planning practice and then illustrates how state-market relations have had an impact on urban spatial outcomes in South Africa's recent history. These insights are then used to describe the spatial development of Cape Town and identifies ineffective and counterproductive interventions and illustrate how economic theories and concepts can be used to inform good planning practice. It concludes with the direction for further research and collaboration between economists and planners to improve planning and policy making in South Africa's cities.